Genomic Characterization and Transcriptomic Profiling of Phospholipase A Superfamily in Cocoa (Theobroma cacao): Genome-wide analysis of the phospholipase A genes in cocoa - Nguyen, Quy Phuong; Vu, Xuan Duong; Chu, Ngoc Thi Bich; Tran, Lan Thi Mai; Chu, Ha Duc; La, Hong Viet; Dong, Huy Gioi; Tran, Huyen Thi Thanh; Cao, Phi Bang (Journal of Tropical Life Science, 2025)
This study investigates the phospholipase A (PLA) superfamily in cocoa (Theobroma cacao), providing a comprehensive analysis of its genomic organization, structural diversity, and functional roles. A total of 19 PLA1 and 20 PLA2 genes were identified, with detailed assessments of their chromosomal locations, protein properties, and exon-intron structures. Phylogenetic analysis established evolutionary relationships with PLA proteins from other species, such as Arabidopsis thaliana and rice (Oryza sativa). Of our interest, transcriptomic profiling under biotic stress caused by Phytophthora megakarya infection and during embryo development revealed distinct expression patterns, demonstrating the involvement of PLA genes in stress responses and key developmental processes. Taken together, these findings provide valuable insights into the roles of PLA genes in cacao biology and offer a foundation for future applications to improve cacao’s resilience and productivity through genetic and biotechnological strategies.